Internet Addiction and Social Interaction among School Adolescents - Sifa Fauziah; Obar Obar; Siti Nursa’adah (Jurnal Penelitian Perawat Profesional, 2026)
The rapid development of information technology has increased internet use among adolescents, which may affect the quality of social interaction in the school environment. This study aimed to analyze the relationship between the level of internet addiction and adolescents’ social interaction at school. A quantitative study with a cross-sectional design was conducted. The sample consisted of 83 students selected using purposive sampling. The research instruments included the Internet Addiction Test (IAT) and a school-based social interaction questionnaire adapted from Diana Rachmawati (2018), in which all items were found to be valid and the reliability of the social interaction instrument showed a Cronbach’s Alpha value of 0.763. Data were analyzed using univariate and bivariate analyses with the Spearman rank correlation test. The results showed that most respondents were female (54.2%) and aged 16 years (51.8%). Most students had a mild level of internet addiction (55.6%), while social interaction was predominantly categorized as poor (50.6%). A significant negative relationship was found between internet addiction and social interaction (r = −0.225; p = 0.041), indicating a weak correlation. In conclusion, higher levels of internet addiction are associated with lower quality of adolescents’ social interaction in the school environment.